Radiation damage in protein crystals examined under various conditions by different methods. - Garman, E; Nave, C (2009)
Investigation of radiation damage in protein crystals has progressed in several directions over the past couple of years. There have been improvements in the basic procedures such as calibration of the incident X-ray intensity and calculation of the dose likely to be deposited in a crystal of known size and composition with this intensity. There has been increased emphasis on using additional techniques such as optical, Raman or X-ray spectroscopy to complement X-ray diffraction. Apparent discrepancies between the results of different techniques can be explained by the fact that they are sensitive to different length scales or to changes in the electronic state rather than to movement of atoms. Investigations have been carried out at room temperature as well as cryo-temperatures and, in both cases, with the introduction of potential scavenger molecules. These and other studies are leading to an overall description of the changes which can occur when a protein crystal is irradiated with X-rays at both cryo- and room temperatures. Results from crystallographic and spectroscopic radiation-damage experiments can be reconciled with other studies in the field of radiation physics and chemistry.